Hygrothermal properties of light-earth building materials. (May 2020) - Colinart, T.; Vinceslas, T.; Lenormand, H.; Menibus, A. Hellouin De; Hamard, E.; Lecompte, T.
Abstract: This experimental study provides complete datasets of hygrothermal properties of numerous hemp-clay with density ranging from 200 to 350 kg m -3 for building thermal insulation. In addition, attention is also paid on protocols and methods, on the measurements repeatability and on the influence of conditioning temperature and relative humidity: mean uncertainties do not exceed 10% for all measurements, while initial conditioning influences at most the results, particularly for the sorption isotherm. Heat and moisture storage properties depend obviously of the constituent (hemp or clay). Furthermore, they can be estimated with a good accuracy with a mixing law. Thermal conductivity of the composites ranges between 0.06 and 0.12 W m -1  K -1 and clearly depends on the density. Water vapor diffusion resistance factor ranges between 2.24 and 4.14, while capillary absorption coefficient ranges between 0.027 and 0.135 kg m -2  s -0.5 . Highlights: Mean experimental errors do not exceed 10%. Drying temperature and relative humidity are the most influencing parameters. Mixing law are validated for estimating heat and moisture storage properties. Thermal conductivity ranges between 0.06 and 0.12 W m -1  K -1 . Water vapor diffusion resistance factor ranges between 2.24 and 4.14. Capillary absorption coefficient ranges between 0.027 and 0.135 kg m -2  s -0.5 .